Anorexia and Bulimia in Adolescence (Research, Society and Development, 2023)
Objective: to understand the main characteristics of anorexia and bulimia in adolescents, through a qualitative literature review, in addition to explaining that an early diagnosis and a family approach are essential for positive long-term results. Methodology: this is a qualitative bibliographic review, based on the selected articles, their results were analyzed and discussed, and a review of the content addressed was presented. According to the following inclusion criteria: in Portuguese, having as main subject eating disorder; 07 articles were selected from the Google Scholar and SciELO databases. Results: the present study observed a relationship between low self-esteem, body dissatisfaction, media influence, social and family aspects are aspects that influence eating disorders, especially anorexia and bulimia. The psychological tretment for patients with anorexia and bulimia aims to help the individual cope with their emotional distress.